Choosing the Company You Keep: Racial Relational Demography Outside and Inside of Work - Wilk, Steffanie L.; Makarius, Erin E. (Organization Science, 2015)
Individuals can differ on demographic characteristics, such as race, from those with whom they interact. This relational demography can lead to poor affiliative outcomes at work when individuals are assigned to work together. However, relationships between dissimilar individuals that occur by choice and develop naturally over time may be of higher quality than those that occur due to structural causes, such as being put together in a work group. In this study, we focus on racial dissimilarity in choice relationships both outside and inside of work and find that greater racial heterogeneity in choice relationships outside of work is related to positive affiliative outcomes at work, such as trust in supervisor and extra-role behaviors, through its effects on relationships inside of the workplace. This has implications for the research on choice and relational demography in organizations, suggesting that relational demography that is a function of choice has benefits for affiliative outcomes at work and that relational demography that is a function of assignment or structure does not. This also contributes to the literature on boundary spanning suggesting that one’s pattern of relational demography of relationships outside of the workplace can spillover and relate to the relationships one develops inside the workplace.